The regulation of circadian entrainment in mice by the adenosine the A2A/A1 receptor antagonist CT1500 - Jagannath, Aarti; Pretoro, Simona Di; Ebrahimjee, Farid; Ftouni, Suzanne; Taylor, Lewis; Foster, Russell G.; Vasudevan, Sridhar (Frontiers in Physiology, 2022)
Circadian entrainment in mice relies primarily on photic cues that trigger the transcription of the core clock genes Period1/2 in the suprachiasmatic nucleus (SCN), thus aligning the phase of the clock with the dawn/dusk cycle. It has been shown previously that this pathway is directly regulated by adenosine signalling and that adenosine A2A/A1 receptor antagonists can both enhance photic entrainment and phase shift circadian rhythms of wheel-running behaviour in mice. In this study, we tested the ability of CT1500, a clinically safe adenosine A2A/A1 receptor antagonist to effect circadian entrainment. We show that CT1500 lengthens circadian period in SCN ex vivo preparations. Furthermore, we show in vivo that a single dose of CT1500 enhances re-entrainment to a shifted light dark cycle in a dose-dependent manner in mice and also phase shifts the circadian clock under constant dark with a clear time-of-day related pattern. The phase response curve shows CT1500 causes phase advances during the day and phase delays at dusk. Finally, we show that daily timed administration of CT1500 can entrain the circadian clock to a 24h rhythm in free-running mice. Collectively, these data support the use of CT1500 in in the treatment of disorders of circadian entrainment.